Penerapan Strategis Pelaksanaa (SP 1) Pemberian Asuhan Keperawatan Jiwa pada Ny. R terhadap Persepsi Halusinasi Pendengaran di Ruang Manggis UPT RSUD Madani Provinsi Sulawesi Tengah: Implementation of Implementation Strategic (SP 1) Delivery Mental Nursing Care on Perception Hearing Hallucinations in the Manggis Room UPT Madani RSUD Palu City - Nandu, Sri Wulandari; Iriani, Indri; Asrum, Muhammad (Universitas Muhammadiyah Palu, 2024)
Mental disorders are patterns of behavior that are currently associated with distress or suffering which creates obstacles in one or more functions of a person's life. Hallucinations come from the Latin word hallucination which means mentally drawing or being dazed. The method used is descriptive. The population in this study were clients who suffered from auditory hallucinations in the Manggis Room at Madani Hospital, Central Sulawesi Province. The research results found from the study of Mrs. R said he often heard voices or whispers calling the client's name, sounds heard when the client was sleeping and alone. The intervention was carried out for 2 days. Data analysis carried out in application shows that after carrying out SP 1 auditory hallucinations the client no longer hears the whispers calling the client's name. From the research results, it was found that the strategic implementation of SP 1, it is hoped that the client can independently control auditory hallucinations to help the client control the hallucinations so as to provide a sense of comfort to the client.